Waste Mixture Utilization as Oyster Mushroom (Pleurotus ostreatus) Growing Media (Jurnal Online Pertanian Tropik, 2022)
Growth media composition needs to be considered because it can affect the growth and development of white oyster mushroom (Pleurotus ostreatus). Wood factory waste in the form of sawdust is commonly used as oyster mushroom’s growth media. However, problem arises when the source of growing media is difficult to access from the cultivation location. There’s a need for an alternative mushroom growing media that is cheap and accessible. Some of them are rice bran, soybean husk, and bagasse which are agricultural wastes. Therefore, this study aimed to obtain the best media composition for oyster mushroom’s growth and production. This study was compiled using one factor completely randomized design (CRD) namely, (M1) 1 kg of sengon sawdust and 1 ounce rice bran; (M2) 1 kg of sengon sawdust and 1 ounce soybean husk; (M3) 1 kg of sengon sawdust and 1 ounce bagasse; (M4) 1 kg of sengon sawdust, ounce rice bran and ounce soybean husk; (M5) 1 kg of sengon sawdust, ounce rice bran and ounce bagasse; and (M6) 1 kg of sengon sawdust, ounce rice bran, ounce soybean husk and ounce bagasse. Result showed that M2 and M4 media composition with soybean husk as one of the constituents was able to increase mushroom’s stem diameter, number of mushroom caps, and the fresh weight of the mushroom. More than ounces of rice bran and soybean husk was more optimal for supporting oyster mushroom growth than < ounces dosage.